1977
DOI: 10.1002/tera.1420160205
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effects of excess glucose on head‐fold rat embryos in culture

Abstract: Rat embryos explanted at nine and one-half days of gestation (early head-fold stages) were cultured for 48 hours in rotating bottles containing rat serum and a gas phase. Addition of 12-15 mg/ml of D-glucose to the culture medium resulted in severe abnormalities and retarded development in a high proportion of embryos, whether or not the osmolarity increase brought about by the addition of glucose was corrected. The raised osmolarity, however, increased the frequency and severity of malformations observed. L-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(95 citation statements)
references
References 16 publications
7
88
0
Order By: Relevance
“…These studies have confirmed that severe malformations can be caused merely by increasing the glucose concentration of the culture medium [68,69]. The chick egg is also malformation-sensitive to glucose and several other sugars during early incubation [70].…”
Section: Fetal Abnormalitiesmentioning
confidence: 79%
“…These studies have confirmed that severe malformations can be caused merely by increasing the glucose concentration of the culture medium [68,69]. The chick egg is also malformation-sensitive to glucose and several other sugars during early incubation [70].…”
Section: Fetal Abnormalitiesmentioning
confidence: 79%
“…Thus, both a high concentration of glucose [9], a low glucose concentration [31] and a high concentration of [3-hydroxybutyrate [32] have been shown to be teratogenic in vitro. Furthermore, various consequences of increased ambient glucose concentration have been suggested to play a role in the disturbed embryogenesis, such as arachidonic acid depletion [33,34], hyperaccumulation of sorbitol [35][36][37][38], deficiency of myo-inositol [36,37,[39][40][41] or alterations in trace metal concentrations of the offspring [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…they were cultured in a high glucose concentration known to cause growth retardation and malformations [9][10][11]. The culture media were supplemented either with citiolone (N-acetyl-DL-homocysteine thiolactone), which is an inducer of oxygen radical scavenging enzymes [12,13], or with superoxide dismutase, catalase or glutathione peroxidase.…”
mentioning
confidence: 99%
“…Environmental insults during this developmental window lead to defects in the cardiovascular system, which subsequently affect the development of several embryonic organs. An in vitro whole embryo culture model permits study of this crucial developmental period and has shown that short exposure to hyperglycemia is teratogenic, causing dose dependent growth retardation, neural tube lesions and yolk sac failure (Cockroft and Coppola, 1977;Pinter et al, 1999;Reece et al, 1996;Rashbass and Ellington, 1988;Sadler, 1980a;Sadler, 1980b;Freinkel et al, 1986). Additionally, this model system mimics the morphological and biochemical vascular defects in the embryo and yolk sac observed in vivo (New et al, 1976;Mills et al, 1979;Sadler and Warner, 1984).…”
Section: Introductionmentioning
confidence: 99%